A Polynomial Chaos Method for Dispersive Electromagnetics (Communications in Computational Physics, 2020)
Electromagnetic wave propagation in complex dispersive media is governedby the time dependent Maxwell's equations coupled to equations that describe theevolution of the induced macroscopic polarization. We consider "polydispersive" materialsrepresented by distributions of dielectric parameters in a polarization model.The work focuses on a novel computational framework for such problems involvingPolynomial Chaos Expansions as a method to improve the modeling accuracy of theDebye model and allow for easy simulation using the Finite Difference Time Domain(FDTD) method. Stability and dispersion analyses are performed for the approachutilizing the second order Yee scheme in two spatial dimensions.